2006
DOI: 10.1029/2005gc001152
|View full text |Cite
|
Sign up to set email alerts
|

Submarine venting of liquid carbon dioxide on a Mariana Arc volcano

Abstract: Although CO2 is generally the most abundant dissolved gas found in submarine hydrothermal fluids, it is rarely found in the form of CO2 liquid. Here we report the discovery of an unusual CO2‐rich hydrothermal system at 1600‐m depth near the summit of NW Eifuku, a small submarine volcano in the northern Mariana Arc. The site, named Champagne, was found to be discharging two distinct fluids from the same vent field: a 103°C gas‐rich hydrothermal fluid and cold (<4°C) droplets composed mainly of liquid CO2. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 41 publications
5
151
0
2
Order By: Relevance
“…The highest CO 2 concentrations, found in the lower Cl fluids at Snowcap and Satanic Mills (Fig. 5.5b, Table 5.2), are among the highest reported to date for vent fluids (Karl et al, 1988;Butterfield et al, 1990;Sakai et al, 1990a,b;Von Damm, 1995;German and Von Damm, 2003;Lupton et al, 2006) and are comparable to those observed in black smoker fluids at the back-arc JADE site, Okinawa Trough (Sakai et al, 1990b). In addition to the higher concentrations relative to Vienna Woods, CO 2 is more 13 C-enriched at PACMANUS, with endmember δ 13 C CO2 values varying from -4.1‰ to -2.3‰ (Table 5.2).…”
Section: H 2 H 2 S Ch 4 Co and Comentioning
confidence: 74%
See 4 more Smart Citations
“…The highest CO 2 concentrations, found in the lower Cl fluids at Snowcap and Satanic Mills (Fig. 5.5b, Table 5.2), are among the highest reported to date for vent fluids (Karl et al, 1988;Butterfield et al, 1990;Sakai et al, 1990a,b;Von Damm, 1995;German and Von Damm, 2003;Lupton et al, 2006) and are comparable to those observed in black smoker fluids at the back-arc JADE site, Okinawa Trough (Sakai et al, 1990b). In addition to the higher concentrations relative to Vienna Woods, CO 2 is more 13 C-enriched at PACMANUS, with endmember δ 13 C CO2 values varying from -4.1‰ to -2.3‰ (Table 5.2).…”
Section: H 2 H 2 S Ch 4 Co and Comentioning
confidence: 74%
“…In stark contrast to the Precambrian shield gases, abiogenic C 1 to C 3 n-alkanes in vent fluids at Lost City are much more 2 H-enriched (δ 2 H of -119 to -171‰, and at odds with the extremely negative δH values of H 2(aq) there (-600 to -700‰, PROSKUROWSKI et al, 2006) by the above reasoning. While these differences could reflect higher temperatures of abiogenesis or mechanistic effects, a likely explanation is that partial or near-complete alkane-water exchange has erased any highly 2 H-depleted signatures.…”
Section: H / 1 H Ratios and Abiogenesis In Igneous Environmentsmentioning
confidence: 87%
See 3 more Smart Citations